A simple and effective approach to fabricate lignin nanoparticles with tunable sizes based on lignin fractionation. Issue 6 (4th March 2020) - Ma, Mingshuai; Dai, Lin; Xu, Jikun; Liu, Zhong; Ni, Yonghao
Abstract : The present study combines nanotechnology with the fractionation technique and presents a facile method for preparing LNPs with desired uniform and small size and lignin valorization. Abstract : In recent years, an increasing number of studies have shown that lignin nanoparticles (LNPs) are a new kind of green and sustainable material with potential applications in many areas. With the development of nanotechnology, the controllable preparation of nanomaterials is necessary. However, lignin heterogeneity remains a hurdle that must be overcome for the controllable preparation of LNPs. To solve this problem, we applied a traditional fractionation technique to the preparation of LNPs. We prepared LNPs with tunable sizes by using different lignin fractions with different molecular weights and hydrophilic group content values. The lignin fraction with a high molecular weight, low content of hydrophilic groups, and high syringyl/guaiacyl ratio resulted in weak lignin–water interactions and a high degree of aggregation within the lignin fraction, thereby producing small LNPs. The prepared LNPs showed controllable sizes (21–139 nm) with very narrow size distributions. The findings support the development of green materials along with nano- and biorefinery technologies.